CHANGES OF CARDIOVASCULAR STABILITY IN CORONARY PATIENTS AND HEALTHY CONTROLS OVER AN INDIVIDUAL YEAR - N. A. Barbarash; N. I. Lazik; V. I. Shaposhnikova; M. V. Chichilenko; S. L. Barbarash; D. N. Kosyagin; O. L. Barbarash (Российский кардиологический журнал)
To determine the influence of an individual year cycle (IYC) lasting from one birthday to another, on the clinical, laboratory and physiological values, we have studies case histories of 330 men with acute coronary pathology and also examined 146 men with Coronary Heart Disease admitted for CABG. 35 almost healthy young men were also examined during a year in different seasons.We have found out that the number of patients developing MI in the XII month of the IYC, was reliably higher that the value for IV-VI months and almost twice as high as the number for the VI month. The severity of MI developing in the XII and I months of the IYC surpassed such in MI developing in other periods of the IYC. In the IV trimester of the IYC (X-XII months) the patients showed a relatively low number of T-cells, the highest cortisol concentration in the saliva, in the III and IV months – T-supressors; in the IV trimester coronary patients showed much less thyroxin, tri-iodothyronin and cortisol than in the I trimester. Blood values in the II trimester of the IYC were consistent with a better prognosis.Healthy young men showed stressed adaptation mechanisms in the IV trimester of the IYC: increased personal alertness (the index of regulatory systems stressing was calculated from a mathematical analysis of heart rate), higher incidence of hypertension, decreased ability to work and immunity. The values in the II trimester were more favorable.The data enable us to draw a conclusion about the universal nature of IYC changes of adaptive parameters of cardiovascular and endocrine systems, which is crucial for preventive cardiology.